In situ TEM probing of crystallization form-dependent sodiation behavior in ZnO nanowires for sodium-ion batteries. (December 2016) - Xu, Feng; Li, Zhengrui; Wu, Lijun; Meng, Qingping; Xin, Huolin L.; Sun, Jun; Ge, Binghui; Sun, Litao; Zhu, Yimei
Abstract: Development of sodium-ion battery (SIB) electrode materials currently lags behind electrodes in commercial lithium-ion batteries (LIBs). However, in the long term, development of SIB components is a valuable goal. Their similar, but not identical, chemistries require careful identification of the underlying sodiation mechanism in SIBs. Here, we utilize in situ transmission electron microscopy to explore quite different sodiation behaviors even in similar electrode materials through real-time visualization of microstructure and phase evolution. Upon electrochemical sodiation, single-crystalline ZnO nanowires (sc-ZNWs) are found to undergo a step-by-step electrochemical displacement reaction, forming crystalline NaZn13 nanograins dispersed in a Na2 O matrix. This process is characterized by a slowly propagating reaction front and the formation of heterogeneous interfaces inside the ZNWs due to non-uniform sodiation amorphization. In contrast, poly-crystalline ZNWs (pc-ZNWs) exhibited an ultrafast sodiation process, which can partly be ascribed to the availability of unobstructed ionic transport pathways among ZnO nanograins. Thus the reaction front and heterogeneous interfaces disappear. The in situ TEM results, supported by calculation of the ion diffusion coefficient, provide breakthrough insights into the dependence of ion diffusion kinetics on crystallization form. This points toward a goal of optimizing the microstructure of electrode materials in order to develop high performance SIBs. Graphical abstract: Ultrafast sodiation of pc-ZNWs benefiting from abundant ion transport pathways among ZnO grain boundaries. Highlights: Single-crystal ZnO nanowires (sc-ZNWs) undergo a stepwise electrochemical sodiation process. The sodiated sc-ZNWs are characterized by a sluggish reaction front and inner heterogeneous interfaces. Poly-crystal ZNWs (pc-ZNWs) have an ultrafast, uniform sodiation speed. There are abundant ionic transport pathways among ZnO nanograins inside the pc-ZNWs. Chemically identical materials could respond differently during electrochemical sodiation, depending on crystallization form.